2014
DOI: 10.1111/eff.12166
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variation in growth and otolith‐inferred field metabolic rates of Canadian young‐of‐the‐year Arctic charr

Abstract: Countergradient variation (CGV) is defined as genetic variation that counteracts the negative influences of the physical environment, minimising phenotypic variability along an environmental gradient. CGV is thought to have relevance in predicting the response of organisms to climate variability and change. To test the hypothesis that growth rate increased with latitude, consistent with CGV, young-of-the-year (YOY) Arctic charr, Salvelinus alpinus, were examined along a~27°latitudinal gradient in central and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 81 publications
(177 reference statements)
2
7
1
Order By: Relevance
“…Similar patterns of growth compensation have been observed in numerous other ectotherms, including fish (Chavarie et al, 2010;Rypel, 2013;Sinnatamby et al, 2015), amphibians (Berven, Gill & Smith-Gill, 1979) and invertebrates (Trussell, 2000;Heilmayer et al, 2005). When the growth compensation is shown to be the result of genetic adaptation, the phenomenon is called counter-gradient variation (Conover & Present, 1990;Conover & Schultz, 1995;Conover, Duffy & Hice, 2009).…”
Section: Discussionsupporting
confidence: 57%
“…Similar patterns of growth compensation have been observed in numerous other ectotherms, including fish (Chavarie et al, 2010;Rypel, 2013;Sinnatamby et al, 2015), amphibians (Berven, Gill & Smith-Gill, 1979) and invertebrates (Trussell, 2000;Heilmayer et al, 2005). When the growth compensation is shown to be the result of genetic adaptation, the phenomenon is called counter-gradient variation (Conover & Present, 1990;Conover & Schultz, 1995;Conover, Duffy & Hice, 2009).…”
Section: Discussionsupporting
confidence: 57%
“…Higher values of M indicate higher metabolic rates, as an increase in metabolic rate results in an increased concentration of metabolically derived carbon in the bloodstream and endolymphatic fluid (Solomon et al, 2006). Values of M at both our sites are high relative to laboratory studies (17-32%) (Høie et al, 2003;Solomon et al, 2006;Tohse & Mugiya, 2008;Elsdon et al, 2010), but overlapped with field-based ranges reported by Sinnatamby et al (2014) Vendace M values were significantly higher in the CE site relative to the ID site, and within the CE site, they were significantly higher than LSR and SSR values. The higher M values for vendace occupying lower temperatures suggest that these M values are driven by activity (e.g.…”
Section: Stable Carbon Isotopessupporting
confidence: 55%
“…In addition to providing insight into dietary resource use, d 13 C oto can be used to make inferences about metabolic rate from the calculation of M, that is the contribution of metabolically derived carbon to d 13 C oto (e.g. Lin et al, 2012;Kahilainen et al, 2014;Sinnatamby et al, 2014). Higher values of M indicate higher metabolic rates, as an increase in metabolic rate results in an increased concentration of metabolically derived carbon in the bloodstream and endolymphatic fluid (Solomon et al, 2006).…”
Section: Stable Carbon Isotopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have used measurements of δ 13 C oto as a proxy for metabolic rate without being able to convert the values into oxygen consumption. Hence, these studies were limited to qualitative estimates of differences in FMR among life stages or groups of fish 41 or correlative studies between δ 13 C oto or M oto and growth rate 42 . Our study calibrates the M oto to measured oxygen consumption and provides strong evidence for the accuracy of this FMR proxy.…”
Section: Discussionmentioning
confidence: 99%